Polyethylene transformation by a psychrotolerant Rhodococcus strain assessed by transcriptomics and 13C-isotope tracing - Anja Werz; Ivano Brunner; Weihong Qi; Matthias Saurer; Marco M. Lehmann; Jan Kühnel; Beat Stierli; Beat Frey (Journal of Hazardous Materials, 2026)

Legal considerations for digital twins in food chain scenarios - Katja Brzezinski-Hofmann; Vincent Korthals Altes; Matthias Brunner (Journal of Consumer Protection and Food Safety, 2026)
Digital twins offer a wide range of potential applications throughout the food supply chain, as demonstrated by the example of determining the suitability for human consumption of pre-packaged minced pork through AI-driven shelf-life assessment. As food business operators, official food control authorities and consumers are open to the use of new technology, there is currently no regulatory need for action regarding the use of AI throughout the food supply chain. However, future regulatory changes, particularly in the area of food labelling, should take into account the specific features arising from the intelligent determination of the use-by date by AI.

First multispecies tree-ring chronologies from the 6th millennium BCE in Southeastern Europe - Maxim Yermokhin; Andrej Maczkowski; Matthias Bolliger; John Francuz; Adrian Anastasi; Krist Anastasi; Ariane Ballmer; Mirco Brunner; Ilirjan Gjipali; Martin Hinz; Marco Hostettler; Johannes Reich; et al. (Dendrochronologia, 2025)

Digital twins in the food supply chain: from concept to application - Christian Fleck; Matthias Brunner; Ulrich Busch (Journal of Consumer Protection and Food Safety, 2025)

Dendroarchaeology at Lake Ohrid: Pine tree-ring chronology and 5th millennium BCE palisades from the pile-dwelling settlement of Lin 3, Albania - Maxim Yermokhin; Andrej Maczkowski; Matthias Bolliger; John Francuz; Adrian Anastasi; Krist Anastasi; Ariane Ballmer; Mirco Brunner; Ilirjan Gjipali; Tryfon Giagkoulis; Martin Hinz; Marco Hostettler; et al. (Dendrochronologia, 2025)

Investigating the storage of organic carbon, nitrogen and phosphorus in pond sediment - Elmar M. Schmaltz; Elisabeth Peham; Hannah Forsthuber; Matthias Konzett; Thomas Brunner; David Ramler; Peter Strauss; Christian Bauer (Journal of Soils and Sediments, 2025)

Evaluating the shelf life of strawberries using a portable Vis-NIR spectrophotometer and a Reflectance Quality Index (RQI) - Laura Rabasco-Vílchez; Francisco Jiménez-Jiménez; Arícia Possas; Matthias Brunner; Christian Fleck; Fernando Pérez-Rodríguez (Postharvest Biology and Technology, 2024)

Efficient injection of gas tracers into rivers: A tool to study Surface water–Groundwater interactions - Théo Blanc; Morgan Peel; Matthias S. Brennwald; Rolf Kipfer; Philip Brunner (Water Research, 2024)

Tracing sources and turnover of soil organic matter in a long-term irrigated dry forest using a novel hydrogen isotope approach - Claudia Guidi; Marco M. Lehmann; Katrin Meusburger; Matthias Saurer; Valentina Vitali; Martina Peter; Ivano Brunner; Frank Hagedorn (Soil Biology and Biochemistry, 2023)

Novel concept to guide systolic heart failure medication by repeated biomarker testing—results from TIME-CHF in context of predictive, preventive, and personalized medicine - Nasser Davarzani; Sandra Sanders-van Wijk; Micha T. Maeder; Peter Rickenbacher; Evgueni Smirnov; Joël Karel; Thomas Suter; Rudolf A. de Boer; Dirk Block; Vinzent Rolny; Christian Zaugg; Matthias E. Pfisterer; et al. (EPMA Journal, 2018)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Isolation and biochemical characterization of underwater adhesives from diatoms - Nicole Poulsen; Nils Kröger; Matthew J. Harrington; Eike Brunner; Silvia Paasch; Matthias T. Buhmann (Biofouling, 2014)